Effects of alfa-hydroxy-isocaproic acid on body composition, DOMS and performance in athletes - Mero, A. A.; Ojala, T.; Hulmi, J. J.; Puurtinen, R.; Karila, T. A.; Seppala, T. (Journal of the International Society of Sports Nutrition, 2010)
Alfa-Hydroxy-isocaproic acid (HICA) is an end product of leucine metabolism in human tissues such as muscle and connective tissue. According to the clinical and experimental studies, HICA can be considered as an anti-catabolic substance. The present study investigated the effects of HICA supplementation on body composition, delayed onset of muscle soreness (DOMS) and physical performance of athletes during a training period.